An exploratory case study on the preparation of undergraduate civil engineering students at the University of Cape Town to contribute to an inclusive society for people with disabilities - McKinney, Victor John (Department of Health and Rehabilitation Sciences, 2016)
Based on the experiences of the researcher who is a quadriplegic, people with disabilities still encounter many challenges within the built environment. As civil engineers play a central role, this study set out to address the question - How are undergraduate Civil Engineering students at the University of Cape Town (UCT) being prepared to contribute to an inclusive society that accommodates people with disabilities? Based on a conceptual theoretical framework that draws from a broader context of the Universal Declaration of Human Rights and the United Nations Convention on the Rights of People with Disabilities, a production line analogy was adopted to explore the resources, approaches and experiences of key stakeholders involved in the preparation of the students. The adopted model recognised the students as the "raw materials", the graduates as the "products", UCT as the "factory", the Engineering Council of South Africa (ECSA) as the "quality controller", the Engineering Industry "utilised and refined" the product, while people with disabilities were the "consumers". A qualitative, exploratory, multiple case design was utilised incorporating interviews with representatives of UCT, the Engineering Industry, and people with disabilities, while the contents of the website of ECSA was reviewed. ECSA has a transformation agenda that does not explicitly identify issues about disability. However, there were opportunities to incorporate the concept of Universal Design (UD) into the exit level outcomes of the undergraduate civil engineering programme. Furthermore, while UCT, Industry and people with disabilities identified legislation around disability as a major resource for the training of students, and UCT and Industry shared an open minded approach to the concept of UD, its inclusion in the education programme is still lacking. There was a conspicuous gap for collaboration between the stakeholders, which seem to hinder the adoption of a multidisciplinary approach in the preparation of the students. The study highlighted the need to formalise a platform that brings the key stakeholders together in the preparation of civil engineering students to contribute to the development of an inclusive society that accommodates people with disabilities.